The Relationship between Positive Thinking and Psychological Health Dimensions in Female Students at the College of Education, Hail University - Almutawaa, Malkah Murdhi (Journal of Educational and Psychological Sciences, 2024)
The aim of this study was to examine the level of positive thinking and the level of dimensions of mental health among female students in the College of Education at Hail University, and to explore the relationship between them. The study followed a descriptive correlational approach, and the study sample consisted of 203 students who were selected using stratified random sampling. The study utilized two instruments: the Positive Thinking Scale developed by Walid Ahmed (2019) and the Mental Health Scale developed by Sayed Youssef (1998). The results of the study revealed a high level of positive thinking among the study sample with a mean score of 3.92, and a high level of mental health with a mean score of 0.82. Furthermore, a statistically significant positive correlation was found between positive thinking and the dimensions of mental health among female students in the College of Education at Hail University, Based on the study’s findings, several recommendations were formulated, including the integration of positive thinking concepts into all curricula according to the academic stage and subject matter, in order to enhance mental health. Additionally, regular conferences should be organized to attract speakers with a positive thinking mindset. Moreover, it is important to encourage students to apply positive thinking concepts in realistic contexts and adopt positive attitudes towards challenges, while also promoting proper preparation for dealing with success and failure. These measures would positively impact their mental health.